BUSINESS ORGANIZATION OF FARMERS IN THE TIMES OF SOCIALAND ECONOMIC INSTABILITY: NEEDS END LIMITATIONS - Hristivoje, Pejčić (Economics of Agriculture, 2007)
Numerous limitations of a successful economic activity make up our current reality. In these circumstances, farmers are insufficiently organized. On the other side, there are needs and possibilities to change this current situation. However, the basic causes of stagnation in this particular case are ignorance and irresponsibility. Political parties can use this state of things with the purpose of defining their offers to a part of the electorate. They can improve their reputation in one part of the electorate by contributing to a better organization of farmers.